Early starts, reversals and catchup in the process of economic development - Areendam Chanda; Louis Putterman (Brown University, Department of Economics, 2004)
Early states like China, India, Italy and Greece have been experiencing more rapid economic growth in recent decades than have later-comers to agriculture and statehood like New Guinea, the Congo, and Uruguay. We show that more rapid growth by early starters has been the norm in economic history, and that the “reversal of fortune” associated with European overseas expansion from about 1500 to 1960 was an exception. We demonstrate that the colonial era reversal was in the process of being reversed in recent decades, and that this second reversal is in line with longer-term trends dating back to the first agricultural revolution.
Keywords: O40; O10; N00; 330; economic growth; economic development; economic history; Wirtschaftswachstum; Entwicklung; Entwicklungskonvergenz; Ländliche Entwicklung; Wirtschaftsgeschichte; Welt